2023
DOI: 10.1001/jamacardio.2023.2167
|View full text |Cite
|
Sign up to set email alerts
|

Association of Longer Leukocyte Telomere Length With Cardiac Size, Function, and Heart Failure

Abstract: ImportanceLonger leukocyte telomere length (LTL) is associated with a lower risk of adverse cardiovascular outcomes. The extent to which variation in LTL is associated with intermediary cardiovascular phenotypes is unclear.ObjectiveTo evaluate the associations between LTL and a diverse set of cardiovascular imaging phenotypesDesign, Setting, and ParticipantsThis is a population-based cross-sectional study of UK Biobank participants recruited from 2006 to 2010. LTL was measured using a quantitative polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Importantly, our study confirms the previously reported causal association between LTL and LVM 16 using 2‐sample MR, which is less susceptible to bias compared with 1‐sample MR. Similarly to Aung et al, 16 who reported a nominally significant effect between LTL and LV stroke volume, there were also significant associations between LTL and LV end‐diastolic and end‐systolic volume, but these did not survive multiple testing correction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, our study confirms the previously reported causal association between LTL and LVM 16 using 2‐sample MR, which is less susceptible to bias compared with 1‐sample MR. Similarly to Aung et al, 16 who reported a nominally significant effect between LTL and LV stroke volume, there were also significant associations between LTL and LV end‐diastolic and end‐systolic volume, but these did not survive multiple testing correction.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study used MR to examine the association between LTL and 7 CMR metrics. 16 The findings indicate that shorter LTL was associated with reduced left ventricular (LV) mass (LVM), reduced LV stroke volume, reduced global ventricular volume, and reduced overall ventricular size. However, only the reduction in LVM would survive multiple testing correction across the 7 explored traits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We considered whether the observed associations between FAI, FEI, and HF risk among women and men could be potentially driven by correlations with some noteworthy biomarkers that were previously found to be related to risk of HF (online supplementary Table S3). 23,26 Among men and women, we found that FAI and FEI had low correlations with LTL, overall BHS and its constituent biomarkers.…”
Section: Correlations Between Free Androgen Free Estradiol and Biomar...mentioning
confidence: 83%
“…In a recent JAMA Cardiology publication, Aung et al performed a large population-based cross-sectional cardiovascular study of middle-aged White adults. The authors reported larger left ventricular mass, volume, and size with longer LTL, which was in turn associated with lower risk of incident heart failure.…”
mentioning
confidence: 99%